تراكيز بعض العناصر النزرة في كبد وعضلات نوعين من الأسماك في نهر الفرات قرب مركز مدينة الناصرية - جنوب العراق: Concentration of some trace elements in liver and muscle of two species of fish in Euphrates River near the center of Al -Nassiriya city- south Iraq - الخفاجي, باسم يوسف (University of Thi-Qar Journal of Science, 2013)
This study involved the estimination of the concentration of four trace elements lead ,cadmium, copper and zinc in liver and muscles of two species of fish Cyprinus carpio and Barbus lutues collected from the Euphrates River near Al-Nassiriya city center south of Iraq during the period from Autumn 2011 to Summer 2012 ,The results showed that the higher concentration of elements (Pb,Cd, Cu, and Zn) were in liver of two species . The present study showed a difference in concentrations of trace elements in liver and muscles of two species of fish, these concentrations varies from one species to another. The tissues of same the species showed differences in concentration of elements, this due to the nature and the function of the tissue and ability of fish on regulating the level of the elements in their bodies during the uptake and elimination processes.The results showed that trace elements concentration in the muscle of two species were in the international acceptable limits, so it can be safely having related to this types of pollutants.